Analisis Bimbingan Konseling Islami Dalam Meningkatkan Motivasi Belajar Pada Mata Pelajaran PAI - Faizah, Nur; Islam, Muhammad Hifdil; Fatimah, Nur (LP3M STIT Al Urwatul Wutsqo Jombang, 2025)
This study aims to analyze the implementation of Islamic counseling guidance in enhancing female students’ learning motivation in Islamic Religious Education (PAI) subjects at SMP Muhammad Shodiq Brani Kulon. Employing a qualitative approach with a case study design, data were collected through observations, in-depth interviews, focus group discussions, and document analysis. The findings reveal that Islamic counseling significantly improves students’ motivation to learn. Motivation transformation is evident in the shift from extrinsic to intrinsic motivation, rooted in spiritual awareness. Counseling techniques such as muhasabah (self-reflection), tadabbur (deep contemplation), and istisyarah (consultation) effectively build students’ self-awareness regarding the value of learning PAI. Furthermore, the role of counselors as spiritual companions and the support of a religious school environment contribute to the program's effectiveness. The study recommends strengthening counselors’ competencies in Islamic counseling and developing media that align with students’ digital culture. These findings contribute to the development of a contextual and transformative model of Islamic counseling in secondary education.